Resistensi Pedagang Kaki Lima Liar terhadap Kebijakan Pemerintah Kota Semarang - Azhari, Muhammad Bachrul; Handoyo, Eko; Setiajid, Setiajid (Unnes Political Science Journal, 2018)
Semarang city is a region that applying the law to the existence of street vendors. Street vendors get protection from the government, one of them by the Regional Regulation of Semarang No. 11 of 2000 on Regulation and Development of street vendors. Article 1 letter F Semarang Regional Regulation No. 11 of 2000 mentions that the street vendors are traders who in an attempt to use tools or equipment that is easy to be overhauled or moved and use the businesses that occupy land held Local Government and or other parties. Issues examined in this study are: (1) What are the factors causing resistance Street Vendor Street Kokrosono and Pleburan. (2) What forms of resistance Lima Street vendors on the street Kokrosono and Pleburan of government policies Semarang. The method used is qualitative. Data was obtained through interviews, observation and documentation. The validity of the data was tested by the method triangulation techniques. Data were analyzed with interactive models through the steps of data collection, data reduction, data presentation, conclusion and verification. The results in this study are as follows: (1) the cause of the Resistance street vendors in Jalan Kokrosono and Pleburan. The cause is due to lack of communication between the government and illegal street traders, so that the desired vendors about where the trade can not be met by the Government of Semarang. (2) forms of resistance Lima Street vendors on the street Kokrosono and Pleburan to Semarang government.